Effect of Ginger (Zingiber officinale) Addition to the Diet on Performance, Serum Parameters and Meat Quality in Male Japanese Quails (Coturnix coturnix Japonica) - Seyit Ahmet Gökmen; Behlül Sevim; Barışcan Curabay; Kübra Ünal; Yusuf Cufadar; Yılmaz Bahtiyarca (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effect of adding ginger powder at different levels (0.0, 0.5, 1.0, 2.0%) to the ration on performance, blood parameters and meat quality characteristics of male Japanese quails. 48 male Japanese quail (Coturnix coturnix Japonica) at 28 days of age were used in the study. The experiment was carried out for 21 days in 4 replications in a quail cage with 12 male Japanese quails in each of 4 treatment groups consisting of rations containing different levels of ginger powder. At the end of the experiment, the effects of adding different levels of ginger powder to male quail diets on the performance and serum parameters studied were statistically insignificant. Pre breast L*, a* and b*, thigh meat colours a* and b* values were not significantly affected by the treatments. However, pre-thigh L* values were significantly lower in the group fed with 2.0% ginger powder compared to the group fed with 0.5% and 1.0% ginger powder. Post breast b* value of the group containing 2.0% ginger powder in the diet was significantly higher than that of the group containing 0.5% and 1.0% ginger powder. It was observed the treatment group containing 2.0% ginger powder significantly decreased the pH value and TBA (thiobarbituric acid number) values at the breast meats when compared to the control group and the treatment group containing 0.5% ginger powder. According to the result of the study, it was observed that the addition of ginger powder to male quail rations did not affect performance and serum parameters, but the use of ginger powder at the level of 2.0% in the diet improved some meat quality characteristics.